Faktor-faktor yang Memepengaruhi Kesejahteraan Masyarakat Pelaku Usaha di Sekitar Obyek Wisata Religi Kubah Datu Abdussamad Marabahan - Maulani, Muhamad Rizal; Maulida, Sri (PPJP Universitas Lambung Mangkurat, 2023)
This type of qualitative research intends to identify the impact of Business Capital Business Capital, Education Level, and the number of Visitors to the Welfare of Business Actors around the Datu Abdussamad Marabahan Dome Religious Attractions. This research uses primary data with techniques to distribute questionnaires to the community of business actors around the Datu Abdussamad Marabahan Dome Religious Attractions. Data analysis techniques in this research use qualitative descriptive analysis by describing data collected narratively. The test's findings in this study stated that the variables of Business Capital, Business Length, Education Level, and Visitor Number funds impact or influence the Welfare of Business Actors around the Datu Abdussamad Marabahan Dome.